Open access practice in personality research: a bibliometric perspective - Pajić, Dejan; Babić, Aleksandra; Jevremov, Tanja (Primenjena psihologija, 2023)
The primary aim of this study was to investigate the structure and dynamics of current research in personality psychology, with a particular focus on open access (OA) practices. A set of 57296 research articles in personality psychology indexed in the Scopus database were analyzed based on their online accessibility: closed (39523), green OA (8770), gold OA (4506), bronze OA (2704), and hybrid gold OA (1793). Although the proportion of OA articles in the overall sample was relatively modest (31%), there has been a consistent upward trend since 2012. Notably, the most significant increase was observed in the proportion of gold OA articles, whereas the number of deposited articles (green OA), not otherwise freely available online, experienced a decline. The knowledge domain of non-OA articles in personality psychology can be broadly delineated into five clusters: (Big Five) personality traits, personality disorders, emotion regulation, Dark Triad/Tetrad, and psychometrics. The emergence of COVID-19 as a “hot” research topic resulted with significant differences in the knowledge domain of non-OA and OA articles. Co-authorship network analysis revealed that authors from Western countries act as the central hub in personality research, though this centrality diminishes when only gold OA articles were taken into account. Gold OA articles performed the worst on most impact and outreach metrics except one, significantly surpassed by green OA articles. As a takeaway, it may be said that although you may need a significant amount of money to do the research, you don’t need it to make your research open and make an impact.